Monitoring training in elite athletes : comparison of coaches' intentions and athletes' experiences - Van Wychen, Shana (My University, 2001)
The structure of training programs is of interest for athletes desiring peak performance. Ideally, the athletes' experiences should be equivalent to the coaches' intentions.
Keywords: Speed skaters - Training of; Athletes - Training of; Coaching (Athletics)